Performance of Quality Protein Maize Under Different Planting Windows - Kumar, Rakesh; Kumar, Sourabh; ., Ashutosh; Singh, Magan; Meena, B.S.; Tomar, S.K.; Datt, Chander; Ram, Hardev; Rathore, D.K. (Indian Journal of Animal Nutrition, 2018)
A field experiment was conducted at Forage Research Block, ICAR-NDRI, Karnal during post rainy season of 2014 and 2015 to study the performance of quality protein maize (QPM) cultivars under different planting windows. The treatments consisted of four sowing times viz., Aug. 15, Sept. 5, Sept. 25 and Oct. 15 inmain plots and five maize cultivars HQPM-1, HQPM-4, HM-10, African tall and J-1006 in subplots in a split plot design. August 15 sowing recorded the maximum plant height, leaf length, leaf width, number of leaves per plant, green fodder yield (53.49 and 56.17 t/ha) and DM yield (11.39 and 12.03 t/ha) during 2014 and 2015, respectively. The performance of Aug. 15 sown maize in post monsoon season was at par with Sept. 5 sowing, however, further delay in sowing led to a significant (P